School Leadership and Educational Change in Singapore - Wong, Benjamin; Hairon, Salleh; Ng, Pak Tee (Springer, 2019)
There is great interest internationally to understand the success of the Singapore education system in the light of its strong and consistent results in international tests, such as PISA, TIMSS and PIRLS. Singapore ranks consistently among the top few countries for Reading, Mathematics and Science (OECD 2014). Interestingly, while some might have previously attributed the good results to rote learning and memorisation, the results of PISA 2012 have offered a different complexion to the issue. When students were assessed on twenty-first-century skills such as problem-solving and flexibility in thinking, Singapore once again performed well (MOE 2014). Notwithstanding its success, the Singapore education system is changing to help prepare its students for the more complex and demanding socio-economic environment of the twenty-first century. It continuously evolves to ensure that their students are well placed and well prepared to meet the emerging demands of a knowledge-driven global economy (MOE 2010; 2013). Under the 1997 umbrella vision of Thinking Schools, Learning Nation (TSLN), many initiatives were subsequently launched. These included National Education (NE), a four-phased ICT Masterplan and the Teach Less Learn More (TLLM) reform. These, and many other initiatives, reflected the system’s transformation to shift the focus of learning from quantity to quality (Ng 2008). Today, the Singapore education system continues its evolutionary path of change by adopting a student-centric, value-driven education paradigm. It aspires to achieve (Heng 2012a):